Meta-Analysis of Cyber Dominance in Modern Warfare: Attacks and Mitigation Strategies (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
This meta-analysis study focused on cyber dominance in modern warfare, particularly, exploring cyber-attacks and mitigation strategies. The study ascertained that the escalating growth of internet connectivity and the rising reliance on networked digital technologies have opened new avenues for cyber-attacks in the contemporary era. Various actors, comprising state and non-state entities, parties in offensive hacking operations and information campaigns to achieve strategic goals. The study conducts a comprehensive meta-analysis of existing research to explore key strategies for establishing and maintaining cyber-attacks and mitigation strategies. This study analyzed peer-reviewed papers that investigate both cyber-attack tactics employed by state actors and defensive policy frameworks and measures adopted by nations. The significant volume of studies indicated that the execution of robust authentication strategies, such as multi-factor authentication (MFA) could mitigate cyberattacks. The meta-analysis studies equally ascertained that consistently employing security patches and software updates is instrumental to addressing these vulnerabilities promptly. Besides, configuring firewalls to limit unnecessary inbound and outbound traffic helps create a strong defense perimeter and prevents unauthorized communication.